Molybdenum‐Based Catalytic Materials for Li–S Batteries: Strategies, Mechanisms, and Prospects. Issue 3 (16th December 2022) - Liu, Yuping; Lin, Zhihua; Bettels, Frederik; Li, Zhenhu; Xu, Jingjing; Zhang, Yulin; Li, Xu; Ding, Fei; Liu, Shuangyi; Zhang, Lin
Abstract : Lithium–sulfur (Li–S) batteries are regarded as promising candidates for high‐energy storage devices because of their high theoretical energy density (2600 Wh kg −1 ). However, their practical applications are still hindered by a multitude of key challenges, especially the shuttle effect of soluble lithium polysulfides (LiPSs) and the sluggish sulfur redox kinetics. To address these challenges, varieties of catalytic materials have been exploited to prevent the shuttle effect and accelerate the LiPSs conversion. Recently, molybdenum‐based (Mo‐based) catalytic materials are widely used as sulfur host materials, modified separators, and interlayers for Li–S batteries. They include the Mo sulfides, diselenides, carbides, nitrides, oxides, phosphides, borides, and metal/single atoms/clusters. Here, recent advances in these Mo‐based catalytic materials are comprehensively summarized, and the current challenges and prospects for designing highly efficient Mo‐based catalytic materials are highlighted, with the aim to provide a fundamental understanding of the sulfur reaction mechanism, and to guide the rational design of cathode catalysts for high‐energy and long‐life Li–S batteries. Abstract : This review aims to present a comprehensive and insightful overview of Mo‐based catalytic materials for Li‐S batteries. The current challenges and prospects in this field are highlighted, providing a fundamental understanding of the sulfur reaction mechanism, and guiding the rational design of cathode catalysts for high‐energy and long‐life Li‐S batteries.